DETERMINANTS OF CONSUMER SATISFACTION WITH SOCIAL COMMERCE - Kojongian, Jovelia; Tendean, Gwyneth; S. Pasuhuk, Lefrand; Mandagi, Deske W. (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the factors that influence consumer satisfaction with social commerce, focusing on service quality, platform type, ease of shopping, and product quality. This study uses a descriptive and causal quantitative design to analyze the relationship between these variables. Data was collected from 257 university students in Manado, Indonesia, who are active consumers of social commerce. Structural Equation Modeling (SEM) was used as the main method in data analysis, with the help of SPSS and SmartPLS software as analysis tools. The results showed that all the factors studied-service quality, platform type, ease of shopping, and product quality-had a positive and significant effect on consumer satisfaction in online shopping. The findings emphasize the importance of optimizing these factors on social commerce platforms to increase customer satisfaction. This study contributes to the literature by providing empirical evidence on the determinants of online shopping satisfaction in the context of Indonesian university students, and offers practical implications for social commerce practitioners to improve user experience and customer loyalty.